From disgusting and complicated to simple and brilliant: implementation perspectives and lessons learned from users and rejectors of mail-in SARS-CoV-2 gargle tests - Röhr, Freda; Uellner, Ferdinand; Deckert, Andreas; Anders, Simon; Burk, Robin; Knop, Michael; Brugnara Kirchmann, Lúcia; Bärnighausen, Till; Jahn, Albrecht; McMahon-Rössle, Shannon A.; Souares-Coutant, Aurélia (Frontiers in Public Health, 2023)
BackgroundDespite the important role of testing as a measure against the COVID-19 pandemic, user perspectives on SARS-CoV-2 tests remain scarce, inhibiting an improvement of testing approaches. As the world enters the third year of the pandemic, more nuanced perspectives of testing, and opportunities to expand testing in a feasible and affordable manner merit consideration.MethodsConducted amid the second pandemic wave (late 2020-early 2021) during and after a multi-arm trial evaluating SARS-CoV-2 surveillance strategies in the federal state Baden-Württemberg, Germany, this qualitative sub-study aimed to gain a deeper understanding of how test users and test rejectors perceived mail-in SARS-CoV-2 gargle tests. We conducted 67 semi-structured in-depth interviews (mean duration: 60 min) via telephone or video call. Interviews were audio-recorded, transcribed verbatim and analyzed inductively using thematic analysis. The Consolidated Framework for Implementation Research guided the findings' presentation.ResultsRespondents generally described gargle sampling as simple and comfortable. However, individual perceptions of the testing method and its feasibility varied widely from disgusting and complicated to simple and brilliant. Self-sampling was appreciated for lowering infection risks during testing, but also considered more complex. Gargle-sampling increased participants' self-efficacy to sample correctly. Communication (first contact, quantity and content of information, reminders, support system) and trust (in the study, its institutional affiliation and test method) decisively influenced the intervention's acceptability.ConclusionUser-driven insights on how to streamline testing include: consider communication, first impressions of tests and information as key for successful mail-in testing; pay attention to the role of mutual trust between those taking and administering tests; implement gargle self-sampling as a pleasant alternative to swab testing; offer multiple test methods to increase test up-take.